FAKTOR POTENSIAL YANG BERPENGARUH TERHADAP KECURANGAN LAPORAN KEUANGAN - Chandra, Jessica Novilia; Mulyani (Lembaga Penelitian dan Pengabdian kepada Masyarakat Institut Bisnis dan Informatika Kwik Kian Gie, 2024)
This research aims to determine the influence of financial targets, financial stability, external pressure, institutional ownership, and ineffective monitoring on indications of the condition of financial reports in manufacturing companies in the food and beverage industry sector. The population in this study used manufacturing companies in the food and beverage industry sector listed on the Indonesia Stock Exchange (BEI) during the 2019 - 2022 period. The sampling technique used purposive sampling technique and produced a sample of 40 companies. The data analysis techniques used are descriptive statistical analysis, pooling test, normality test, multicollinearity test, autocorrelation test, heteroscedasticity test, customized r2, F test, and t test. Based on the research results, it shows that financial targets, financial stability, external pressure, institutional ownership and ineffective monitoring have no effect on the condition of financial statements.